2018
DOI: 10.3390/jfmk3040062
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a High-Protein Diet on Bone Mineral Density in Exercise-Trained Women: A 1-Year Investigation

Abstract: The effects of long-term high-protein consumption (i.e., >2.2 g/kg/day) are unclear as it relates to bone mineral content. Thus, the primary endpoint of this investigation was to determine if consuming a high-protein diet for one year affected various parameters of body composition in exercise-trained women. This investigation is a follow-up to a prior 6-month study. Subjects were instructed to consume a high-protein diet (>2.2 g/kg/day) for one year. Body composition was assessed via dual-energy X-ray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Mediated by a higher insulin secretion, tryptophan is transported across the blood chain barrier and hence, stimulates the synthesis and function of neurotransmitters (e.g., serotonin) as a dietary precursor (Wurtman et al, 2003). However, there seems to be a ceiling effect as seen in athletes who are used to a steady protein supplementation (Antonio et al, 2019b). With that being said, we conclude that a high-protein moderate energy restriction (ER group) may have beneficial effects on sleeping quality which might be greater by trend than a high-protein intake alone (CG).…”
Section: Sleepmentioning
confidence: 99%
“…Mediated by a higher insulin secretion, tryptophan is transported across the blood chain barrier and hence, stimulates the synthesis and function of neurotransmitters (e.g., serotonin) as a dietary precursor (Wurtman et al, 2003). However, there seems to be a ceiling effect as seen in athletes who are used to a steady protein supplementation (Antonio et al, 2019b). With that being said, we conclude that a high-protein moderate energy restriction (ER group) may have beneficial effects on sleeping quality which might be greater by trend than a high-protein intake alone (CG).…”
Section: Sleepmentioning
confidence: 99%
“…Once again, the habitual intake of these subjects (1.5±0.2 g/kg) was well above the general recommendation of 0.8 g/kg. A follow-up study was conducted by Antonio and colleagues in which female subjects followed a high (>2.2 g/kg/day) protein diet for one year 31 . In line with the previous study, no significant differences were observed in body composition or bone density for the duration of the study.…”
Section: High Protein Intake (>22 G/kg/day)mentioning
confidence: 99%
“…The increased caloric intake reported in these studies was primarily the result of increasing dietary protein intake. It has been theorized the lack of statistically significant differences in body composition and body mass during a hypercaloric diet is due to the thermic effect of protein [27][28][29][30][31][32] . Diet-induced thermogenesis is greatest for protein which contributes to an increase in total daily energy expenditure [32][33][34] .…”
Section: High Protein Intake (>22 G/kg/day)mentioning
confidence: 99%
“…Higher protein diets (> 2.0 g/kg/day) have been shown to be important for maintaining LM and resting energy expenditure under periods of intentional and unintentional caloric restriction [59], which may be more prevalent among active women. Additionally, high-protein diets (> 2.2 g/kg/ day) have not resulted in any adverse effects to bone mineral density or kidney function in healthy women after 6 months [60] or 1 year [61]. As a result of the potentially greater protein oxidation, particularly in the LP, active women should focus on consuming high-quality protein sources (e.g., high biological value, high digestibility, absorption, and EAA content) to minimize muscle soreness and breakdown.…”
Section: Protein Supplementation Considerationsmentioning
confidence: 99%